PENGARUH PERENCANAAN SUMBER DAYA MANUSIA (SDM) DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DI YAYASAN DARUL HIJRAH PUTERI BANJARBARU - Rafikah Rafikah; Khuzaini Khuzaini; Mohammad Zainul (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2020)
To improve employee performance, it is necessary to have a good and right human resource planning, so that human resources in an institution really have the capacity and competence in accordance with what is needed by the organization. The purpose of this study was to determine whether or not there was a significant effect of human resource planning and competency on the performance of employees in Darul Hijrah Female Banjarbaru foundation. The purpose of this study was to determine whether or not there was a significant effect of human resource planning and competency on the performance of employees in Darul Hijrah Female Banjarbaru foundation. The type of research used is Explanatory Research, using quantitative methods. The samples used were 63 employees at Darul Hijrah Female Banjarbaru Foundation, the data collected using questionnaires, the analysis technique used was multiple linear regression, with the help of the SPSS For Window 24 program.Partially HR Planning does not affect the performance of employees because the t-value of -0.842, because t count> t table (1.96) is -0.842 <1.96, then H0 is accepted H1 is rejected. Which means that Human Resource Planning does not affect the performance of employees at Darul Hijrah Female Banjarbaru Foundation. And with a significance value of 0.403> 0.05.Whereas Competence has a significant effect on the performance of Darul Hijrah Puteri Banjarbaru foundation employees with t count of 3.694, because t count> t table (1.96) which is 3.694> 1.96, then H1 is accepted H0 is rejected, which means that competence has a significant effect on performance Employee of Darul Hijrah Female Banjarbaru Foundation. Simultaneously (F) shows F count of 7.119 with significance of 0.002 thus Fcount> F table, which is 7.119> 5.608, then H0 in H1 is accepted, meaning HR planning (X1) and Competence (X2) has simultaneous influence on employee performance.